Psycho-oncology - Holland, Jimmie C. (New York : Oxford University Press, 2010)
Psycho-Oncology was the first comprehensive text in the field of psychosocial oncology and remains the gold standard today. Written by 67 internationally known psychiatry and palliative care experts, the resource is truly an essential reference for all providers of palliative care.
Zweigstelle: Medizinische Bibliothek
Exemplar/Standort: QZ 260 Psych (MedBib) / Klin. Psychologie
Exemplar/Standort: Medizinische Bibliothek
Text in engl. Sprache
Keywords: Psychoonkologie; Klinische Psychologie; Krebs <Medizin>; Onkologie; Lehrbuch